Corrigendum: Development of Thermosensitive Ophthalmic in situ Gels of Bimatoprost for Glaucoma Therapy - Corrigendum (Indian Journal of Pharmaceutical Education and Research, 2025)
Based on the authors' description the following figures are to be considered: Figure 7 has been updated and replaced with the corrected version provided below.
Keywords: Corrigendum